Ufbp1, a Key Player of Ufm1 Conjugation System, Protects Against Ketosis-Induced Liver Injury via Suppressing Smad3 Activation - Chen, Fanghui; Sheng, Le; Xu, Chenjie; Li, Jun; Ali, Ilyas; Li, Honglin; Cai, Yafei (Frontiers in Cell and Developmental Biology, 2021)
The dairy cattle suffer from severe liver dysfunction during the pathogenesis of ketosis. The Ufm1 conjugation system is crucial for liver development and homeostasis. Ufbp1 (Ufm1 binding protein) is a putative Ufm1 target and an integral component, but its role in ketosis-induced liver injury is unclear so far. The purpose of this study is to explore the key role of Ufbp1 in liver fibrosis caused by ketosis in vivo and in vitro. Liver tissues were collected from ketotic cows and Ufbp1 conditional knockout (CKO) mice in vivo. While Ufbp1-/- mouse embryonic fibroblast cells (MEFs) and Hela cells were used for vitro validation. Subsequently, various assays were performed to reveal the underlying molecular mechanisms of Ufbp1 protective effect. In this study, hepatic fibrosis, endoplasmic reticulum (ER) stress and apoptosis were reported in the liver of ketotic cows, fibrotic markers (α-SMA, Collagen1), ER stress markers (GRP78, CHOP) were upregulated remarkably, and the apoptosis-related genes (Bcl2, Bax) were in line with expectations. Interestingly, Ufbp1 expression was almost disappeared and Smad2/Smad3 protein was largely phosphorylated in the liver of ketotic cows, but Ufbp1 deletion caused Smad3 phosphorylation apparently, rather than Smad2, and elevated ER stress was observed in the CKO mice model. At the cellular level, Ufbp1 deficiency led to serious fibrotic and ER stress response, Smad3 was activated by phosphorylation significantly and then was translocated into the nucleus, while p-Smad2 was largely unaffected in MEFs. Ufbp1 overexpression obviously suppressed Smad3 phosphorylation in Hela cells. Ufbp1 was found to be in full combination with Smad3 using endogenous immunoprecipitation. Taken together, our findings suggest that down-regulation or ablation of Ufbp1 leads to Smad3 activation, elevated ER stress, and hepatocyte apoptosis, which in turn causes liver fibrosis. Ufbp1 plays a protective role in ketosis-induced liver injury.